Glass Fiber Post lengths and adhesive strategies to restore extensively damaged canines (Research, Society and Development, 2022)
The aim of this study was to evaluate different post lengths and adhesive strategies for restoring extensively damaged canines. Sixty human canines were randomly distributed into two groups (n=30), according to the resin cement used: self-adhesive or conventional.  Each group was further distributed into 3 groups (n=10) based on the intracanal post lengths: 5, 7.5 and 10 mm. The radicular portion was endodontically filled, the cervical third was enlarged to simulate extensive damage and the coronal portion was reconstructed with composite resin. The samples were prepared with a simulated periodontal ligament and submitted to fatigue loading (160N – 1,200,000 cycles), followed by fracture resistance testing. The results were submitted to two-way ANOVA and Tukey tests (α=5%). The assessed glass fiber post lengths have not influenced on the fracture resistance (p>0.05). However, the performance of the conventional cements was better than the self-adhesive cements when the same post length was compared (p